Reviving the RNA World: An Insight into the Appearance of RNA Methyltransferases - Rana, Ajay K.; Ankri, Serge (Frontiers in Genetics, 2016)
RNA, the earliest genetic and catalytic molecule, has a relatively delicate and labile chemical structure, when compared to DNA. It is prone to be damaged by alkali, heat, nucleases or stress conditions. One mechanism to protect RNA or DNA from damage is through site-specific methylation. Here, we propose that RNA methylation began prior to DNA methylation in the early forms of life evolving on Earth. In this article, the biochemical properties of some RNA methyltransferases (MTases), such as 2’-O-MTases (Rlml/RlmN), spOUT MTases and the NSun2 MTases are dissected for the insight they provide on the transition from an RNA world to our present RNA/DNA/protein world.